Accessing the Subway in Toronto, Canada: Access Mode and Catchment Areas. Issue 1 (2016) - Xi, Yang (Luna); Saxe, Shoshanna; Miller, Eric
A buffer of ½ mi (805 m) is commonly used to define the service area of a subway (metro) station. This buffer is based on an approximation of the distance people are willing to walk to access the subway. This research compared the ½-mi pedestrian catchment area with the service areas reported in the Transportation Tomorrow Survey for access to the Toronto Transit Commission Subway System in Canada. This paper assesses the breakdown of access by mode to the subway and the pedestrian, bus–streetcar, and automobile catchment areas of stations in Toronto. This analysis finds two major drawbacks with the use of the ½-mi pedestrian catchment area. The service areas of buses and streetcars that connect to the subway are critical; they account for more than a third of all riders. Spatially, the size and the shape of the service area predicted by the ½-mi approach do not accurately represent what is observed in Toronto. Pedestrian catchment areas are commonly less than ½ mi in radius, and the bus–streetcar and automobile catchment areas are often many times larger.